The formation of the ius commune and humanism (Revista da Faculdade de Direito, Universidade de São Paulo, 2018)
The main goal of this paper is to present the legal medieval science, developed in universities along the Late Middle Ages, that resulted in the formation of the ius commune, as well as the changes produced by the humanist jurisprudence.